Observation of the critical state to multiple-type Dirac semimetal phases in KMgBi - Liu, D. F.; Wei, L. Y.; Le, C. C.; Wang, H. Y.; Zhang, Xin; Kumar, N.; Shekhar, Chandra; Schroter, N. B. M.; Li, Y. W.; Pei, Ding; Xu, L. X.; Dudin, P.; et al. (Journal of Applied Physics, 2021)
Dirac semimetals are classified into different phases based on the types of Dirac fermions. Tuning the transition among different types of Dirac fermions in one system remains a challenge. Recently, KMgBi was predicted to be located at a critical state in which various types of Dirac fermions can be induced owing to the existence of a flatband. Here, we carried out systematic studies on the electronic structure of KMgBi single crystals by combining angle-resolve photoemission spectroscopy and scanning tunneling microscopy/spectroscopy. The flatband was clearly observed near the Fermi level. We also revealed a small bandgap of ∼20 meV between the flatband and the conduction band. These results demonstrate the critical states of KMgBi that transition among various types of Dirac fermions can be tuned in one system.
CRIS-Team Scopus Importer:2022-04-14